2006
DOI: 10.1002/gcc.20371
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genome and transcriptome analysis of the 11q13 amplicon in human oral cancer and synteny to the 7F5 amplicon in murine oral carcinoma

Abstract: 11q13 amplification occurs in a wide variety of tumors, including almost half of oral squamous cell carcinomas (OSCC) where it has been correlated with a poor outcome. In this study, we compiled 3.6 Mb of DNA sequence in the 11q13 amplicon core and refined the physical map of the amplicon. In the process, we determined the genomic structure and normal tissue expression patterns of two recently identified genes, TAOS2/TMEM16A and MRGF, which reside in the amplicon core. We then quantified DNA copy number and mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 46 publications
10
111
2
1
Order By: Relevance
“…[132][133][134] The coding sequence for ANO1 is located on amplicon 11q13, which contains the coding sequence for several proteins related to cell cycle, proliferation and apoptosis, and which is often amplified in cancers with poor prognosis. 118,[135][136][137][138] ANO1 is upregulated in several cancer tissues including head and neck squamous cell carcinoma, prostate, breast, pancreatic cancer and gastrointestinal stromal tumor cells. 120,[139][140][141][142] Figure 14A and 14B show overexpression of ANO1 at the mRNA level and the protein level, respectively, in PDAC cells compared to normal human pancreatic ductal epithelium cells (HPDE).…”
Section: Anoctamin1 -Ano1mentioning
confidence: 99%
“…[132][133][134] The coding sequence for ANO1 is located on amplicon 11q13, which contains the coding sequence for several proteins related to cell cycle, proliferation and apoptosis, and which is often amplified in cancers with poor prognosis. 118,[135][136][137][138] ANO1 is upregulated in several cancer tissues including head and neck squamous cell carcinoma, prostate, breast, pancreatic cancer and gastrointestinal stromal tumor cells. 120,[139][140][141][142] Figure 14A and 14B show overexpression of ANO1 at the mRNA level and the protein level, respectively, in PDAC cells compared to normal human pancreatic ductal epithelium cells (HPDE).…”
Section: Anoctamin1 -Ano1mentioning
confidence: 99%
“…The 11q13 amplicon contains a stretch of proteins related to cell cycle, proliferation and apoptosis (cyclin D1, ORAOV1, FGF19, FGF4, TMEM16A, Fas-associated via death domain, PPFIA1, cortactin) [20]. The complex structure of this amplicon has mostly been studied in breast cancer, where multiple genes have been suggested as driver genes [21,22].…”
Section: Ano1 Is Located On the 11q13 Ampliconmentioning
confidence: 99%
“…13 72 have shown that all but four of 13 genes in the 11q13 amplicon core are overexpressed and this expression appears to be coordinated. 85 We proposed that 11q13 amplification may be driven by a cassette of genes that provide growth or metastatic advantage to cancer cells. This is supported by the finding that the human 11q13 amplicon core is syntenic to mouse chromosomal band 7F5, which is frequently amplified in chemically-induced murine OSCC.…”
Section: Gene Amplificationmentioning
confidence: 99%
“…85,86 Due to the identification of genome-wide nonrandom genetic events in OSCC by classical cytogenetic, CGH, and now cDNA microarrays, targeted studies assessing the significance of amplification and overexpression of other genes within the 11q13 amplicon may allow for the elucidation of other key genes associated with HNSCC progression. Further investigation of the biochemical pathways impacted by 11q13 amplification and distal 11q loss are in progress.…”
Section: Gene Amplificationmentioning
confidence: 99%